Mechanisms of the anti-hypertensive effect of Hibiscus sadariffa L. calcyes - Ajay, M.; Chai, H.J.; Mustafa, A.M.; Gilani, A.H.; Mustafa, Mohd Rais (2007)
Previous studies have demonstrated the anti-hypertensive effects of Hibiscus sabdariffa L. (HS) in both humans and experimental animals. To explore the mechanisms of the aDti-hypertensive effect of the HS, we examined the effects of a crude methanolic extract of the calyces of HS (HSE) on vascular reactivity in isolated aortas from spontaneously hypertensive rats. HSE relaxed, concentration-dependently, KCI (high K+, 80 mM)and phenylephrine (PE, 1 mu M)-pre-contracted aortic rings, with a greater potency against the alpha(1)-adrenergic receptor agonist. The relaxant effect of HSE was partly dependent on the presence of a functional endothelium as the action was significantly reduced in endothelium-denuded aortic rings. Pretreatment with atropine (1 mu M), L-NAME (10 mu M) or methylene blue (10 mu M), but not indomethacin (10 mu M), significantly blocked the relaxant effects of HSE. Endothelium-dependent and -independent relaxations induced by acetylcholine and sodium nitroprusside, respectively, were significantly enhanced in aortic rings pretreated with HSE when compared to those observed in control aortic rings. The present results demonstrated that HSE has a vasodilator effect in the isolated aortic rings of hypertensive rats. These effects are probably mediated through the endothelium-derived nitric oxide-cGMP-relaxant pathway and inhibition of calcium (Ca2+)-influx into vascular smooth muscle cells. The present data further supports previous in vivo findings and the traditional use of HS as an anti-hypertensive agent. (c) 2006 Elsevier Ireland Ltd. All rights reserved.